Uncovering the Neuroprotective Effect of Hedysarum multijugum Maxim-Chuanxiong Rhizoma Compound on Cerebral Infarction through Quantitative Proteomics. (26th March 2022) - Wang, Guozuo; Zeng, Xiaomei; Yang, Kailin; Gong, Shengqiang; Ge, Anqi; Liu, Wenlong; He, Qi; Zhang, Wenhao; Ge, Jinwen
Abstract : Objective . To uncover the neuroprotective effect of Hedysarum multijugum Maxim - Chuanxiong Rhizoma compound (Huangqi-Chuanxiong Compound (HCC)) on cerebral infarction (CI) through quantitative proteomics. Method . CI model was established by the modified Zea Longa intracavitary suture blocking method. After modeling, the rats were given intragastric administration for 7 days, once a day. After the 7-day intervention, the neurological function score was performed, the brain tissue was pathologically observed, and the total serum protein was extracted. Then, these proteins were analyzed by LC-MS/MS to identify the differentially expressed proteins (DEPs) in the HCC/CI group and CI/sham operation group. Finally, bioinformatics analysis was used to analyze DEPs, including gene ontology (GO) analysis, pathway analysis, and protein interaction analysis. ELISA and Western blotting were used to verify the proteomics results. Result . The neurological function scores of the HCC group were lower than those of the CI group. HE staining showed that the pathological results of the HCC group were improved. A total of 1340 proteins were identified by LC-MS/MS, of which 1138 proteins contain quantitative information. There are 122 DEPs in the CI/sham operation group and 25 DEPs in the HCC/CI group with fold change >1.3 or <0.77 and FDR<0.05. The 12 upregulated proteins in HCC/CI group include Protein Actn2, Kelch-like protein 41, Alpha-1, 4 glucan phosphorylase, Protein Lrtm2, Dystrophin, Galectin-1, and C4b-binding protein beta chain. The 13 downregulated proteins include Alpha-2 antiplasmin, Arachidonate 15-lipoxygenase, Carbonic anhydrase 2, Complement factor I, angiotensinogen, catalase, Protein LOC103691744, and Anionic trypsin-1. The bioinformatics analysis showed that HCC may treat CI through regulating cell-substrate adhesion and regulation, reactive oxygen species metabolic process, angiotensin response (cellular response to angiotensin), positive regulation of the occurrence of nerves and neurons (positive regulation of neurogenesis), inflammatory response, response to hypoxia (response to hypoxia, response to decreased oxygen levels), and cellular calcium homeostasis (cellular calcium ion homeostasis). The results of ELISA and Western blot also showed that, compared with model group, the angiotensinogen and catalase in HCC group were decreased (P < 0.05 ), which is consistent with the findings of proteomics. Conclusion . The therapeutic mechanism of HCC in the treatment of CI may involve fibrinolysis, cell-matrix adhesion, inflammation, hypoxia, and oxidative stress.